The Status Of Quality Assurance Management Practicing in Higher Education - Eisa Faraj; Mustafa Abdullah (University of Science and Technology, Yemen, 2013)
ا Abstract: This study aimed at introducing the concept of total quality management and its application in the filed of higher education on the grounds that it is one of the most important development sectors. Moreover, it aimed at identifying the reality of the application of total quality management by the Libyan Universities as seen by the academicians. It took into consideration the requirements of the organizational culture , academic status administrative and financial situation , it also aimed at realizing a high level of quality in the output of university education in line with the requirements of the labor market Study population consisted of all the faculty members at Libyan public universities . A stratified random sample was selected . The sample consisted of (201) members . Study's tool namely questionnaire were distributed over the sample members, (181) of them came back or (90%) . Averages , standard deviations , and alpha - Cronbach , were used to verify the stability of the study fields performance as a whole . Ttest was used to test the hypotheses . After analyzing the data , the study concluded that the level of applying total quality management in Libyan universities is high . As to viewpoint of academicians , There are statistically significant differences between the application reality of TQM in the Libyan universities and the required level of TQM application . it showed a degree of (58.8%) , while administrative and financial situation was moderately met (65.4%) . The level of meeting the needs of the labor market came in second rank of importance . Finally , the organizational culture is at a low level (52.2%) , this indicates that the Libyan universities still lack the basic necessary requirements for the successful implementation of total quality management .